STUDI PERBANDINGAN METODE EKSPLISIT DAN IMPLISIT DALAM PENYELESAIAN PERSAMAAN DIFERENSIAL STABILITAS TRANSIEN SISTEM TENAGA LISTRIK - Hardianto, Triwahju
Abstract : This thesis explores the implicit method used to solve the differential equations of transient stability in electric power system. Some papers described that the implicit method produces the better solutions than those produced by the explicit method in solving the stiff differential equations in electric power system. In the implicit methods, Trapezium method is a general method used to solve differential equations of electric power system. In. this thesis we attempt to solve differential equation by using Euler implicit method. It is shown that, in some cases, Euler implicit: method is better than Trapezium implicit method with respect to its accuracy as well as its speed.